Transfer function based input impedance determination of triple active bridge converter - Yang, Jiajun; Buticchi, Giampaolo; Gu, Chunyang; Gunter, Sandro; Yan, Hao; Wheeler, Pat (2019)
The concept of multiport dc-dc converter was proposed to reduce the conversion stages of dc microgrid on more electric aircraft (MEA). The structure of multiport dc-dc converter is basically developed from the dual active bridge (DAB) converter because of its galvanic isolation and bidirectional power flow. A power electronics converter as a key element of the electrical power distribution system may cause stability issues. To address these challenges, the impedance characteristic of the multiport converter will be analyzed. In this paper, a transfer function based small signal model is developed and validated with a switching model, to figure out the characteristic of input impedance of triple active bridge (TAB) converter. Preliminary experimental results are presented to be as a support.